2012
DOI: 10.1186/1748-717x-7-69
|View full text |Cite
|
Sign up to set email alerts
|

Functional dosimetric metrics for predicting radiation-induced lung injury in non-small cell lung cancer patients treated with chemoradiotherapy

Abstract: BackgroundRadiation-induced lung injury (RILI) is an important dose-limiting toxicity during thoracic radiotherapy. The purpose of this study is to investigate single photon emission computed tomography (SPECT) perfusion-weighted functional dose-volume histogram (FDVH) for predicting RILI in non-small cell lung cancer (NSCLC) patients treated with definitive chemoradiotherapy.MethodsFifty-seven locally advanced NSCLC patients receiving chemoradiotherapy were enrolled prospectively. Patients had treatment scans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…Hoover et al retrospectively reviewed SPECT/CT-based perfusion/ventilation lung parameters of patients undergoing thoracic radiotherapy, and their data suggested a higher sensitivity and specificity with perfused mean lung dose for radiation pneumonitis correlation (AUC = 0.81), compared to standard dose-volume constraints (AUC ≤ 0.73) [22]. Wang et al echoes similar results, showing high correlation of perfusion metrics with radiation-induced lung injury and spatial differences between anatomic lung V 60Gy and perfused lung V 60Gy [23]. Recent data also showed that patients who had perfused-MLD > 16 Gy, perfused V 20Gy > 30%, and perfused V 30Gy > 23% went on to develop radiation pneumonitis [16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hoover et al retrospectively reviewed SPECT/CT-based perfusion/ventilation lung parameters of patients undergoing thoracic radiotherapy, and their data suggested a higher sensitivity and specificity with perfused mean lung dose for radiation pneumonitis correlation (AUC = 0.81), compared to standard dose-volume constraints (AUC ≤ 0.73) [22]. Wang et al echoes similar results, showing high correlation of perfusion metrics with radiation-induced lung injury and spatial differences between anatomic lung V 60Gy and perfused lung V 60Gy [23]. Recent data also showed that patients who had perfused-MLD > 16 Gy, perfused V 20Gy > 30%, and perfused V 30Gy > 23% went on to develop radiation pneumonitis [16].…”
Section: Discussionmentioning
confidence: 95%
“…In addition to investigations on baseline SPECT/CT imaging prior to radiation therapy [16,22,23], other studies have also correlated changes between pre- and post-treatment functional lung imaging and its relationship to radiation pneumonitis. Farr et al noted a higher risk of symptomatic pneumonitis in those patients who had a reduction in perfusion at 3 months post-radiotherapy compared to patients who did not, with a relative risk estimate of 3.6 [24].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a few studies have recently proposed novel models to quantify or predict normal tissue radiation toxicity using functional information from FDG-PET (8), single photon emission computed tomography perfusion (34,35), and DCE-MRI (36). These studies, that propose new metrics as the metabolic dose, functional dose or bio-dose, show an emerging interest toward an innovative approach to RT that integrates into the treatment strategies the individual differences in tumor biology and radiation sensitivity of normal tissues (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Usually in dose escalation protocols, for reasons of tolerability, doses are determined by dose constraints for normal tissues, not by features relevant for tumor control as e.g. tumor size [3,6,7,17-19]. As a consequence large tumors are often treated with smaller doses than small tumors and presumably high volume tumors are occasionally excluded from enrolment in protocols.…”
Section: Discussionmentioning
confidence: 99%